Nonperturbative phenomena in field theory and gravity, and use of Borel summation to capture nonperturbative information - Rahman, Md Ashiq (BRAC University, 2018)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Science in Physics.